Do Transfer Pricing Laws Limit International Income Shifting? Evidence from European Multinationals - Theresa Lohse; Nadine Riedel (Center for Economic Studies and ifo Institute (CESifo), 2013)
In recent years several countries have augmented their national tax laws by transfer pricing legislations which intend to limit the leeway of multinational firms to exploit international corporate tax rate differences and relocate profit to low-tax affiliates by distorting intra-firm transfer prices. The aim of this paper is to empirically investigate whether these laws are instrumental in restricting shifting behaviour. To do so, we exploit unique information on the scope and evolution of national transfer pricing laws and link it with panel data on European multinationals. In line with previous studies, we find evidence for tax-motivated profit shifting. The analysis further suggests that transfer pricing rules significantly reduce shifting activities. The effect is economically relevant, suggesting that the legislations may be socially desirable despite the high administrative burden they impose on firms and tax authorities.
Keywords: H25; F23; 330; corporate taxation; international profit shifting; transfer pricing laws